Liability of public authority entities under art. 4172 of the Polish Civil Code - Jaworski, Bartłomiej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The issue of liability of public authorities involves a lot of fundamental problems of a constitutional, axiological and philosophical nature, while tracing its dynamic evolution – especially in recent years – both nationally and internationally, shows that it reflects to some extent the nature of the relationship between the State and an entity and allows the identification of the ongoing changes in legal thinking and functioning of the new democratic mechanisms. In the Polish legal system, entities that exercise public authority have to reckon with the need to continuously incur liability. However, in accordance with Article 4172 of the Polish Civil Code, bodies of public authority are responsible for damages caused by their legal activities, and if the damage was caused to a person, the victim may claim full or partial redress and financial compensation for the inflicted damage, when circumstances indicate that equity so requires. The principle expressed in Article 4172 is increasingly applied in the cases of damages to the State and other broadly defined entities of public authorities and is an issue worth closer analysis for the possibility of its use by citizens who have suffered injury through the legal action of administrative entities.
Keywords: public authority liability; liability of public authority entities for legal actions; principle of equity